Independent impact of glycemia ad blood pressure in albuminuria on high-risk subjects for metabolic syndrome - Rosenbaum, Paulo; Gimeno, S. G A; Sanudo, A.; Franco, L. J.; Ferreira, S. R G; de Barros Jr., Newton; Hirai, A. T.; Kikuchi, M.; Cardoso, M. A. [UNESP]; Tomita, N.; Chaim, R.; Wakisaka, K. (My University, 2004)
Background: Microalbuminuria may reflect diffuse endothelial damage. Considering that diabetes and hypertension cause vasculopathy, we investigated associations of albumin-to-creatinine ratio (ACR) with plasma glucose and blood pressure levels in high-risk subjects for metabolic syndrome. Methods: A sample of 519 (246 men) Japanese-Brazilians (aged 60 ± 11 years), who participated in a population-based study, had their ACR determined in a morning urine specimen. Backward models of multiple linear regression were created for each gender including log-transformed values of ACR as dependent variable; an interaction term between diabetes and hypertension was included. Results: Macroalbuminuria was found in 18 subjects. ACR mean values for subjects with normal glucose tolerance, impaired fasting glycemia, impaired glucose tolerance and diabetes were 9.9 ± 6.0, 19.0 ± 35.4, 20.7 ± 35.4, and 33.9 ± 55.0 mg/g, respectively. Diabetic subjects showed higher ACR than the others (p < 0.05). An increase in the proportion of albuminuric subjects was observed as glucose metabolism deteriorated (4.9, 17.0, 23.0 and 36.0%). Stratifying into 4 groups according to postchallenge glycemia (< 7.8 mmol/l, n = 9 1; ≥ 7.8 mmol/l, n = 4 10) and hypertension, hypertensive and glucose-intolerant subgroups showed higher ACR values. ACR was associated with gender, waist circumference, blood pressure, plasma glucose and triglyceride (p < 0.05); albuminuric subjects had significantly higher levels of such variables than the normoalbuminuric ones. In the final models of linear regression, systolic blood pressure and 2-hour glycemia were shown to be independent predictors of ACR for both genders (p < 0.05). In men, also waist was independently associated with ACR. No interaction was detected between diabetes and hypertension. Conclusions: These findings suggest that both glucose intolerance and hypertension could have independent but not synergistic effects on endothelial function - reflected by albumin loss in urine. Such hypothesis needs to be confirmed in prospective studies. © 2004 Dustri-Verlag Dr. K. Feistle.
Keywords: Albuminuria; Blood pressure; Glucose intolerance; Metabolic syndrome; albumin; creatinine; glucose; triacylglycerol; adult; aged; anthropometry; blood pressure measurement; Brazil; controlled study; deterioration; diabetes mellitus; diet restriction; endothelium; female; gender; glucose blood level; glucose intolerance; glucose metabolism; glucose tolerance; high risk patient; human; hypertension; Japan; linear regression analysis; major clinical study; male; metabolic syndrome X; microalbuminuria; population research; provocation test; sampling; statistical analysis; statistical model; systolic blood pressure; triacylglycerol blood level; urinalysis; Aged; Analysis of Variance; Chi-Square Distribution; Creatine; Diabetes Mellitus, Type 2; Female; Glucose Tolerance Test; Humans; Hypertension; Linear Models; Male; Middle Aged; Risk Factors